2020
DOI: 10.1007/s12264-020-00484-9
|View full text |Cite
|
Sign up to set email alerts
|

Microglia-Derived NLRP3 Activation Mediates the Pressor Effect of Prorenin in the Rostral Ventrolateral Medulla of Stress-Induced Hypertensive Rats

Abstract: Increased microglial activation and neuroinflammation within autonomic brain regions such as the rostral ventrolateral medulla (RVLM) have been implicated in stress-induced hypertension (SIH). Prorenin, a member of the brain renin-angiotensin system (RAS), can directly activate microglia. The present study aimed to investigate the effects of prorenin on microglial activation in the RVLM of SIH rats. Rats were subjected to intermittent electric foot-shocks plus noise, this stress was administered for 2 h twice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 55 publications
(85 reference statements)
0
30
0
Order By: Relevance
“…It has further been shown that Ang II microinjection into the mouse RVLM results in increased BP (Sasaki and Dampney, 1990), an effect that is reversed by administration of an Ang II receptor antagonist (Ito and Sved, 1996;Dampney et al, 2002;Ito et al, 2002). The PRR is present in the RVLM of mice (Contrepas et al, 2009;Li et al, 2012;Xu et al, 2016) and rats (Hu et al, 2020). In addition, blocking the PRR with the peptide PRO20 (Li et al, 2015b) attenuates neuroinflammation and decreases BP and renal sympathetic nerve activity in these animals (Hu et al, 2020), establishing a major role for the RVLM-PRR in hypertension development.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has further been shown that Ang II microinjection into the mouse RVLM results in increased BP (Sasaki and Dampney, 1990), an effect that is reversed by administration of an Ang II receptor antagonist (Ito and Sved, 1996;Dampney et al, 2002;Ito et al, 2002). The PRR is present in the RVLM of mice (Contrepas et al, 2009;Li et al, 2012;Xu et al, 2016) and rats (Hu et al, 2020). In addition, blocking the PRR with the peptide PRO20 (Li et al, 2015b) attenuates neuroinflammation and decreases BP and renal sympathetic nerve activity in these animals (Hu et al, 2020), establishing a major role for the RVLM-PRR in hypertension development.…”
Section: Discussionmentioning
confidence: 98%
“…The PRR is present in the RVLM of mice (Contrepas et al, 2009;Li et al, 2012;Xu et al, 2016) and rats (Hu et al, 2020). In addition, blocking the PRR with the peptide PRO20 (Li et al, 2015b) attenuates neuroinflammation and decreases BP and renal sympathetic nerve activity in these animals (Hu et al, 2020), establishing a major role for the RVLM-PRR in hypertension development. Our current study demonstrates that RVLM-PRR immunoreactivity in the HTN human is significantly higher than that in NTN subjects, indicating the potential clinical importance of the PRR in the RVLM in human hypertension development.…”
Section: Discussionmentioning
confidence: 99%
“…We recorded RSNA when the general procedures for acute experiments were ready, the RSNA recording method was adapted from our previous study [5]. In anesthetized rats (urethane 800 mg/kg and αchloralose 40 mg/kg ip), the right formal artery was catheterized for the recording of BP and HR using a Powerlab system (AD Instruments).…”
Section: Bp Measurements and Rsna Recordingmentioning
confidence: 99%
“…In SIH, multiple mechanisms have been proposed and sympathetic nervous system (SNS) hyperactivity has emerged as a major culprit [3]. Within the cardiovascular sympathetic regulatory centre, local enhanced reninangiotensin system (RAS) activity and augments SNS output, thereafter results in a sustained elevation of arterial blood pressure (BP) [4].This is also con rmed by several animal studies that demonstrate microinjection of prorenin (a precursor of RAS cascade) directly activates sympathetic hyperactivity whereas microinjection of prorenin antagonist attenuates the hypertensive effect [5,6]. Generally, SNS output elevates BP via direct stimulation of sympathetic nerve innervating cardiovascular organs, or via indirect enhancement of release of vasopressinergic hormones involved in salt, volume, and cardiovascular regulation [7].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation